The Ugandan hip-hop image: the uses of activism and excess in fragile sites. Issue 3 (December 2020) - Singh, Simran
Abstract: This article discusses the characteristics of image in Ugandan hip-hop with a particular focus on representations of activism and excess. Locating Uganda as a fragile site on the basis of widespread political, social and economic marginalisation, this examination considers members of Uganda's first generation of hip-hop artists, to argue that both activism and excess act in singular response to these circumstances. Finding articulation in strivings for economic freedom and social justice, the Ugandan hip-hop image reveals negotiations of histories of colonialism and of contemporary neoliberal capitalism: in doing so, it raises intersections of race and gender, informed by hip-hop's significance as a multi-billion-dollar global industry. This cross-disciplinary inquiry combines ethnomusicology with media, cultural and visual studies in dialogue with political economy.